Negotiating Muslim Interfaith Marriage in Indonesia: Integration and Conflict in Islamic Law - Mohamad Abdun Nasir (Mazahib, 2022)
Conflict can emerge from marriage involving parties of a different faith. However, interfaith marriage may also expose negotiation to secure the union. Although interfaith marriage is normatively restricted in Islamic law, it does occur. This study departs from the normative discourse of Islamic law and the empirical research of Muslim family law. It uses the theory of law, conflict, and integration to analyse the textual debates and practice of interfaith marriage in Lombok, Indonesia. This study reveals the patterns of Muslim interreligious marriage and the conversion that applies. The first pattern shows that non-Muslim partners convert to Islam before the marriage can be concluded. The second pattern involves Muslims who leave Islam to marry their non-Muslim partner. The third pattern suggests that each couple adheres to a different belief during the marriage even though the marriage contract was performed according to Islamic law. From the perspective of Islamic law, in the sense of sharia and Muslim family code, the first pattern is the most ideal because it follows these Islamic legal normativities. Although all practices have the potential for family and social integration, the second pattern is the most susceptible to conflict. Keywords: interfaith marriage, conflict, integration, Islamic law